Teachers' Strategies in Improving Multicultural Aspects in Islamic Religious Education Learning - Achmada, Hasna'Rizqia; Pratama, Havidz Cahya (LPPI, 2023)
The Indonesian nation is one of the largest multicultural countries in the world because it has various ethnic groups and cultures, various languages and religious beliefs. So multicultural education is needed, namely education that respects differences so that conflict and division do not occur. This attitude of mutual respect will create dynamic cultural diversity and richness which is the nation's identity and must be maintained. One of the main goals of multicultural education is to combat discrimination and racism in society. By introducing students to diversity and opening their minds to different ways of life, beliefs, multicultural education can also help create a more tolerant and inclusive society. The method used in this research is to use the literature study method, namely a research method by searching for or obtaining data appropriate to the topic from relevant literature, whether from books, scientific articles or journals. With the results and discussion of this research, namely First, understanding Multiculturalism in the context of Islamic Religious Education. Second, the use of inclusive learning methods, teachers need to use inclusive learning methods to ensure active participation and positive learning experiences for all students, without distinguishing based on cultural background. Third, building understanding and tolerance between religions, teachers must encourage understanding and tolerance between religions in the classroom. Fourth, building problem solving and critical thinking skills, teachers can encourage students to develop problem solving and critical thinking skills through case studies and discussions involving multicultural issues in the context of Islamic religious education.